Synthetic small molecules that induce neuronal differentiation in neuroblastoma and fibroblast cells1. Issue 10 (15th October 2015) - Halder, Debasish; Kim, Gun-Hee; Shin, Injae
<x xml:space="preserve">Abstract</x> Imidazole-based synthetic small molecules promote neurogenesis in readily available and simply manageable neuroblastoma and fibroblast cells.